Seasonal yield and composition of an inland artisanal fishery in a humic floodplain ecosystem of Central Kalimantan, Indonesia - SULMIN GUMIR; ARDIANOR ARDIANOR; SYAHRINUDIN SYAHRINUDIN; GUSTI Z. ANSHARI; YUKIO KOMAI; KAZUO TAKI; HARUKUNI TACHIBANA (Society for Indonesian Biodiversity, 2018)
Gumiri S, Ardianor, Syahrinudin, Anshari GZ, Komai Y, Taki K, Tachibana H. 2018. Seasonal yield and composition of an inland artisanal fishery in a humic floodplain ecosystem of Central Kalimantan, Indonesia. Biodiversitas 19: 1181-1185. Seasonal yield of an inland artisanal fishery was studied in 2015 in the Takapan Floodplain Lake located along the Rungan River of Central Kalimantan Province-Indonesia. Record on daily fish catch consisting weight data and species composition was made in situ along with a one-year rainfall data that was collected from the nearest Meteorological Station located in Palangka Raya City airport. Results showed that throughout the year, total annual yield of captured fishes reached 4.8 tons comprised of 34 commercial freshwater fish species. Seasonal yield varied considerably in which fish capture was higher during the rainy season than on the dry season. The transition period from rainy to dry season was found to be the peak period of fish capture in the floodplain. Of the 34 fish species, the most abundant species was Channa striata that accounted to almost 50% of total annual fish yield. The two most abundant fishes, Channa striata, and Kryptopterus palembangensis were a top predatory blackfish and an omnivorous surface water whitefish, respectively. This result indicated that the studied floodplain habitat was still in good condition, however, conservation is needed to maintain the sustainability of freshwater fish resource in the future.